PENGARUH KETERSEDIAAN SDM, PERILAKU KEPEMIMPINAN, DAN PEMBERDAYAAN KERJA TERHADAP LOYALITAS KERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN LINGGA - Marlissawaty, Fikky; Sardi, Muhamad; Hendra, Hendra; Herman, Hendri; Nugraha, Andika (Berajah Journal, 2024)
This study aims to analyze the effect of human resource availability, leadership behavior, and work empowerment on employee job loyalty at the Lingga Regency DPRD Secretariat. The research method used is quantitative method with data collection techniques through questionnaires distributed to all employees. The analytical tool used in this research is SPSS version 28.0, which helps in processing and analyzing data. Simultaneous tests were carried out using the F test to determine the joint influence of the independent variables on the dependent variable. The F test results show that HR availability, leadership behavior, and work empowerment significantly affect employee job loyalty. Partial test (t test) was conducted to determine the effect of each independent variable individually. Partial test results show that HR availability, leadership behavior, and work empowerment have a significant positive effect on employee work loyalty. This research shows that increasing the availability of adequate human resources, leadership with positive behavior, and effective employee empowerment contribute significantly to employee loyalty. Thus, organizations are expected to pay more attention to these aspects in an effort to improve employee loyalty and performance. The results of this study provide important insights for agency leaders to prioritize more effective human resource management and focus on employee empowerment.